New Circumpapillary Retinal Nerve Fiber Layer Thickness and Bruch’s Membrane Opening-Minimum Rim Width Assessment in Nonglaucomatous Eyes with Large Discs - Serife Bayraktar; Gulnar Sultanova; Zafer Cebeci; Emre Altinkurt; Belgin Izgi (Journal of Ophthalmology, 2019)
Purpose. To compare the new spectral-domain optical coherence tomography (SD-OCT) algorithm for measuring circumpapillary retinal nerve fiber layer (RNFL) thickness centered on Bruch’s membrane opening (BMO), RNFLBMO1, with the conventional circumpapillary RNFL thickness measurement centered on the optic disc (RNFLDİ), and assess the BMO-minimum rim width (BMO-MRW) in nonglaucomatous eyes with large discs. Methods. This prospective, cross-sectional, observational study included a total of 91 eyes of 91 patients having nonglaucomatous eyes with large discs (Group 1) and 50 eyes of 50 healthy subjects (Group 2). The optic nerve head (ONH) parameters obtained by confocal scanning laser ophthalmoscopy (CSLO), peripapillary RNFL thickness, BMO area, and BMO-MRW were imaged with SD-OCT. Results. The mean disc size was 3.06 ± 0.42 mm2 (range, 2.61–4.68) in Group 1 and 1.95 ± 0.23 mm2 (range, 1.6–2.43) in Group 2 (p=0.0001). The mean BMO area was 2.9 ± 0.58 mm2 (range, 1.26–4.62) in Group 1 and 2.05 ± 0.31 mm2 (range, 1.51–2.82) in Group 2 (p=0.0001). The difference between RNFLDİ and RNFLBMO1 measurements in Group 1 was stronger than in Group 2 because it was significant in all sectors in large discs. The mean global BMO-MRW thickness was significantly thinner in large discs; it was 252.95 ± 42.16 µ (range, 170–420) in Group 1 and 326.06 ± 73.39 µ (range, 210–440) in Group 2 (p=0.0001). There was a positive correlation between BMO-MRW thickness measurements and RNFL thickness parameters, both with RNFLDİ and RNFLBMO1, in global and all optic nerve sectors except temporal quadrants with r = 0.257–0.431 (p≤0.001–0.01) in Group 1. But in control group, Group 2, there was a weak correlation or no correlation between BMO-MRW thickness measurements and RNFL thickness parameters with r = −0.256–0.328 (p=0.797–0.02). Conclusion. The new circumpapillary RNFL scanning algorithm centered on BMO is better to assess the RNFL thickness and BMO-MRW in large discs for the early diagnosis of glaucoma.